Status Quo of Progress Testing in Veterinary Medical Education and Lessons Learned - Herrmann, Lisa; Beitz-Radzio, Christina; Bernigau, Dora; Birk, Stephan; Ehlers, Jan P.; Pfeiffer-Morhenn, Birte; Preusche, Ingrid; Tipold, Andrea; Schaper, Elisabeth (Frontiers in Veterinary Science, 2020)
Progress testing is an assessment tool for longitudinal measurement of increase in knowledge of a specific group, e.g. students, which is well known in medical education. This article gives an overview of progress testing in veterinary education with a focus on the progress test of the German-speaking countries. The ‘progress test veterinary medicine’ (PTT) was developed in 2013 as part of a project by the Competence Centre for E-Learning, Didactics and Educational Research in Veterinary Medicine – a project cooperation of all German-speaking institutes for veterinary medicine in Germany, Austria and Switzerland. After the end of the project, the PTT was still continued at six locations, at each of the five German schools for veterinary medicine and additionally in Austria. Further changes to the PTT platform and the analysis were carried out to optimize the PTT for continuing to offer the test from 2017 to 2019. The PTT is an interdisciplinary, formative electronic online test. It is taken annually and is composed of 136 multiple-choice single best answer questions. In addition, a ‘don’t know’ option is given. The content of the PTT refers to the day one competencies described by the European Association of Establishments for Veterinary Education. The platform Q-Exam ® Institutions (IQuL GmbH, Bergisch Gladbach, Germany) is used for creating and administrating the PTT questions, the review processes and organizing of the online question database. After compiling the test by means of a blueprint, the PTT file is made available at every location. After the last PTT in 2018, the link to an evaluation was sent to the students from four out of these six partner universities. The 450 analyzed questionnaires showed that the students mainly use the PTT to compare their individual results with those of fellow students in the respective semester. To conclude our study, a checklist with our main findings for implementing progress testing was created.